(untitled) (Ghana Journal of Science, Technology and Development, 2023)
Data seems to suggest that smallholder’s share of area under cultivation in Ghana and Africa in general, is declining while medium-scale farms are increasing rapidly. Without any empirical evidence, there is a perception that the rapid growth in the share of medium-scale farms would ursher in an Asia-like green revolution, where technology revolution expanded access to modern inputs and led to dramatic increase in farm productivity and food production. This paper explored the question of whether farm size increases especially from small-scale to medium-scale farms led to increase in farm productivity. Using data from 420 maize farmers in Northern Ghana, and the estimation of a naïve, semi-log and stochastic frontier models, the paper tested the farm-size-productivity hypothesis and explored the factors that influence farm output and input use efficiency. The paper found the presence of inverse farm-productivity relationship in maize farming. While value of farm output increased with farm size, input use efficiency followed a quadratic pattern with small farms being more efficient than medium-scale farms and large-scale farms being more efficient than small- and medium-scale farm operation. The paper concluded that, smallholder farmers were not able to transfer their productive efficiency from small-scale to medium-scale levels. This reality needs to be considered in government’s agricultural modernisation policy.